CALORIFIC VALUES AS FUNCTIONS OF MAIN BODY CONSTITUENTS IN SOME FRESHWATER TELBOSTS - Pal, B B; Pal, G P (Indian Journal of Fisheries, 2011)
Energy values of groups of small, medium and large size fishes of tomecommeircially importEnt freshwater fishes have been determined using wet-oxidationmethod. The calorific values per unit of dry weight was significantly different(P